It s kind of expected that the woman does everything : Exploring the anticipated work-family conflict perceptions and attitudes of South African Hindu women - Garach, Darshana (Organisational Psychology, 2025)
Anticipated work-family conflict (AWFC) is an emerging phenomenon, increasingly experienced among young women. Hindu women, in particular, anticipate forms of workfamily conflict as they tend to follow traditional gender roles pre-determined in their culture, such as the role of being the primary caregiver. Hence, many Hindu women may compromise work responsibilities for family and caring responsibilities. Young Hindu women often grapple with the pervasive influence of gender roles, stereotypes, and career expectations, which may lead to potential AWFC. Through semi-structured, in-depth interviews with ten young Hindu women in South Africa, this study provides insight into their perceptions and attitudes toward AWFC. Thematic analysis was utilised to examine the data, delving into the participant's insights and perspectives to gain a comprehensive understanding of their lived experiences. The study findings highlighted the dilemmas these Hindu women were exposed to, as well as the coping strategies they relied on to resolve work-family interface challenges. Three key themes emerged that illustrated their lived reality: (1) Navigating work-family interface dilemmas: Perspectives of Hindu women, (2) Coping mechanisms: Strategies for addressing anticipated work-family challenges among Hindu women, and (3) Hindu women seeking community and support: Navigating the work-family interface. Through these findings, recommendations for improving workplace support for young Hindu women are presented.